Geoprocessamento na modelagem parametrizada da paisagem territorial: aplicações da geovisualização na simulação da paisagem urbana - Sheyla Aguilar de Santana (2014)
This work aims to build knowledge on the theory and production of urban space considering the social functions of the city and the needs of contemporary urban reforms. It is understood that contemporary reforms are structured from two possible logical. The first driven by entrepreneurship backed by shares of public-private interests that seek growth and economic competitiveness of the city. Are pointual transformations through speculative construction in the area. The second approach, on a much slower process, is grounded in the changes concerning the role and actions of the urban planning regulations. In this aspect, the performances in the production of the landscape are the responsibility of government and legal instruments have parameters with different scales of urban planning and management. The study of support decision making with a focus on facilitating the decoding of the language of urban parameters systems becomes critical to the development of this thesis. The axis of the contribution of this thesis is grounded in creating and proposing a three-dimensional methodological route simulation of urban landscapes with a focus on volumetric approach between the realities of the built city , the projected city - shaped by laws and urban parameters - and the perceived city - created from mental maps of their territory by citizens . The focus is to build a bridge between city x real cool city with a view to support the proposition of modeling and analysis for landscape planning and management actions in addition to bringing a visual tool that allows the user to have a new perspective of perception and recognition of space lived, with a view to assisting the various actors in the perception of space encourage the sharing of decision making. In this sense, one of the pillars of this thesis is the geoprocessing techiniquies that has being contributing to the development of applications, scenarios and simulations of landscapes that assist in decision making in urban intervention process. This work aims to make a review on the state of the art GIS in urban planning, the new challenges of representation of the territory, the models and modeling for urban environments to introduce new concepts, paradigms, methodologies and techniques for urban planning and management . Was chosen to work with three-dimensional models since it has been a tool with great potential for communication landscape and a way of decoding the urban language for the various actors in town. It was clear that the three-dimensional models allow a better view of the landscape potential approved by regulatory together planners and technicians responsible for the consent of urban actions. The benefits of moving work of two-dimensional data to three-dimensional data are depicted in this thesis through an illustrative test with a small group to validate the proposed model. In practice stage, the methodological route will be explored in detail since it is at this stage where is concentrated the major contribution of this work. The first step will be to show how it was done building the three-dimensional base from two-dimensional data or raw data. The reasons and justifications for the choice of system that involves the application of new converging concepts from geographic information systems and building infrastructure modeling will also be presented. We will show how the assembly of three-dimensional geographic information system was conducted. At a later stage, you can see the methodological procedures for carrying out simulations and creating volumetric scenarios beyond the ways feedback system underpinning proposals for further intervention, management and restrictions on urban space. The results of these simulations were inserted in three different systems and environments for conducting interactivity, usability, communication and immersion tests and evaluation of the gain information from both the proposed model and the systems used to disseminate this three-dimensional information . Throughout this process, new tools and concepts such as Geocollaboration, for the acquisition of spatial data have been used through the use of collective intelligence and knowledge and voluntary basis for the generation of three-dimensional data as a way to decrease the value and efforts in assembly process of the geographic database. Also in this thesi , a review was made of the proposed methodology for verifying whether you can reapply the same script to other cities in Brazil and the world . This step is done and some propositions presented new techniques as an alternative route in the replication process of this methodology here proposed. The results, shown through three interfaces to aid in visualization of existing city and planned to assess, with a group of tests, the perception of the city , the interpretation of urban parameters, the importance of visualization in urban modeling, to identify areas conducive to urban growth and the recognition that the city in fact modeled by the parameters is only one that goes through the approval of projects , because the informal city is much larger and more expressive than legal.